Falla cardíaca crónica etapa B (2016)
ABSTRACT: Congestive heart failure is classically defined as a clinical syndrome. Early detection of patients at high risk and of those with asymptomatic ventricular dysfunction, which by definition do not meet the criteria, has become an effective treatment strategy. For that reason they have been included in the classification and the clinical practice guidelines. Methodology: In order to create the clinical practice guideline based on evidence, we followed the steps defined in the Methodological Guide for the Preparation of Clinical Practice Guidelines and Economic Evaluation in the General System of Social Security of the Colombian Ministry of Health and Social Protection. Results: In this issue we present the recommendations to treat heart failure with asymptomatic left ventricular dysfunction. Conclusion: Some therapeutic strategies change the prognosis of patients with heart failure stage B. Early detection and treatment are important in patients at high risk.